PENGARUH EKSPOR MINYAK KELAPA SAWIT TERHADAP PERTUMBUHAN EKONOMI INDONESIA TAHUN 2014-2023 - Bonaraja Purba; Dwi Atika Zahra; Khairunnisa Umi Almas; Sabrina Erisa Aulia Sihotang; Siti Mardiah (Institut Teknologi dan Bisnis Dewantara, 2025)
This study aims to evaluate the extent to which palm oil exports contribute to national economic growth during the period 2014-2023 and to identify the factors influencing this relationship. The data used is sourced from the In the analysis, the author employs a simple regression method to examine the relationship between palm oil exports and economic growth. The testing includes both partial and simultaneous influence analyses. The entire data processing procedure is conducted using SPSS version 25 software, ensuring the accuracy and validity of the research results. It is found that the variable of palm oil exports on economic growth has an F-value of 5.485, an F-table value of 0.188, and a significance value of 0.047 < 0.05. Thus, it can be concluded that there is a simultaneous influence between palm oil exports and economic growth. In the t-test results, the calculated t-value (2.342) is greater than the t-table value (1.85955), with a significance of 0.034 < 0.05. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (H1) is accepted. Palm oil exports have a positive and significant influence; when palm oil exports increase, economic growth also experiences an increase.